2020
DOI: 10.3892/ol.2020.11895
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of COL8A1 indicates poor prognosis across human cancer types and promotes the proliferation of gastric cancer cells

Abstract: Gastric cancer (GC) was one of the most common types of the digestive system. COL8A1 was reported to be associated with cancer progression. The present study showed COL8A1 was overexpressed and correlated to shorter overall survival (OS) time across human cancer types. Specially, our results showed COL8A1 was up-regulated in advanced stage GC compared to low stage GC samples. Higher expression of COL8A1 was significantly correlated to shorter OS time in patients with GC. Bioinformatics analysis revealed COL8A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…There are very few studies of COL8A1 in gastric cancer. Experiments on gastric cancer cells show that the silence of COL8A1 can obviously inhibit cell proliferation, migration, and invasion in GC [ 31 ]. We have verified through immunohistochemical analysis that the expression of COL8A1 in GC tissues is distinctly higher than that in normal tissues, and COL8A1 is significantly related to pathological T staging and lymph node metastasis, which suggests that COL8A1 expression may play a part in the progression of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies of COL8A1 in gastric cancer. Experiments on gastric cancer cells show that the silence of COL8A1 can obviously inhibit cell proliferation, migration, and invasion in GC [ 31 ]. We have verified through immunohistochemical analysis that the expression of COL8A1 in GC tissues is distinctly higher than that in normal tissues, and COL8A1 is significantly related to pathological T staging and lymph node metastasis, which suggests that COL8A1 expression may play a part in the progression of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the four identified markers in the model, elevated expression of COL8A1 has been found in CAFs and was significantly associated with a high risk of death in head and neck squamous cell carcinoma (Lai et al, 2019). Zhang et al identified COL8A1 as the prognostic hub gene highly correlated with Wnt2, which is elevated selectively in CAFs, and high coexpression of COL8A1 and Wnt2 was an independent adverse prognostic factor for colon cancer patients (Katoh, 2001;Zhang et al, 2020) proliferation and promoted the apoptosis of GC cells (Zhou et al, 2020). As for SPOCK1, studies have proved SPOCK1 as an EMT-related marker that was closely correlated with tumorigenesis and invasiveness in gastric cancer (Yan et al, 2017;Chen et al, 2018), prostate cancer (Wang et al, 2016), pancreatic cancer (Li et al, 2020), gallbladder cancer (Shu et al, 2015), and lung cancer (Miao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The gene COL8A1 is highly expressed in GC and is associated with shorter overall survival. Collagen, type VIII, alpha 1 (COL8A1) participates in the malignant biological behavior of GC by promoting the proliferation of GC cells and inhibiting their apoptosis [ 28 ]. The transmembrane prostate androgen-inducible protein 1 (PMEPA1) is a single-pass transmembrane protein that is functionally involved in the TGF-β signaling pathway.…”
Section: Discussionmentioning
confidence: 99%